Nutritional Risk Screening Tools in Hospitalised Children - Moeeni, Vesal; Day, Andrew S (International Journal of Child Health and Nutrition, 2012)
In clinical practice, the assessment of nutritional status in children can be problematic. More than one indicator is often required: these may include anthropometric measurements, body compartment analysis and biochemical markers. The nutritional status of children at the time of admission to hospital can impact adversely on their hospital stay. Furthermore, children’s medical conditions may also impact upon their nutrition during a hospital stay. In recent years a number of Nutrition Risk Screening (NRS) tools have been developed and validated, with the goals of providing rapid assessment of children’s risk of nutritional change during a hospitalisation. This article reviews the current NRS tools, considers their benefits and shortcomings and evaluates the potential roles of these tools